ANALISIS KEBIJAKAN PENDIDIKAN DI PONDOK PESANTREN: TANTANGAN DAN STRATEGI PENGEMBANGAN - Alwi, Wildan; Akasyah, Dudi; Marhamah, Marhamah; Puadah, Popi; Furqon, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to examine the education policy in Islamic boarding schools in facing the challenges of globalization by highlighting the role of Law No. 18 of 2019. A qualitative approach is used in this study, with literature studies as a method of collecting and analyzing data related to Islamic boarding school education policies. The results of the study indicate that Islamic boarding school education policies are regulated in Law No. 18 of 2019, which consists of nine chapters and 55 articles. The policy covers five main aspects: institutional forms, Islamic boarding school education objectives, funding sources, quality assurance, and education levels. In addition, globalization has a significant impact on Islamic boarding schools, especially in giving rise to apathy and a culture of laziness among students. Therefore, efforts are needed to develop the potential of students through the use of science and technology. The process of formulating Islamic boarding school education policies can be carried out through five stages: agenda setting, policy formulation, implementation, evaluation, and policy improvement. This study is expected to contribute as a reference in understanding Islamic boarding school education policies in depth and help formulate strategic steps in developing Islamic boarding school education policies in the era of globalization. The results of the study show that educational policies in Islamic boarding schools tend to focus on the tradition of teaching yellow books but are starting to adapt by including a formal curriculum.